Confessional poetry and music - Vancu, Radu (Primerjalna književnost, 2015)
The study examines the works of two foremost confessional poets: the American John Berryman, with his deep interest in Bach, and the Romanian Mircea Ivanescu, with his lifelong obsession for Chopin, observing how, though greatly interested in music, they shared the same diffidence towards it.
Keywords: Berryman, John, 1914-1972; Ivanescu, Mircea, 1931-2011; književnost in glasba; ameriška poezija; romunska poezija; osebnoizpovedna lirika; Trauma; travma